2002
DOI: 10.2139/ssrn.322800
|View full text |Cite
|
Sign up to set email alerts
|

The Dominant Role of "Local" Information in the User Innovation The Case of Mountain Biking

Abstract: 1.0: Introduction and overviewFirms that manufacture products and services have an incentive to develop innovations that appeal as strongly as possible to as wide a customer base as possible in order to enhance their innovation-related profits. Research into the incentives operating on user-innovators, however, leads us to hypothesize that this category of innovators will display a very different pattern.Prior research has shown that users that develop new products and services typically profit only from their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 27 publications
4
54
0
1
Order By: Relevance
“…Some studies have explored the effectiveness of the theory with regard to identifying any user innovations. Thus, Franke and Shah (2003), Lüthje (2004), Lüthje et al (2002) and Morrison et al (2000) divided their samples into innovators and non-innovators as a dependent variable, and showed that lead user characteristics are systematically different in these two groups via t-tests and logit analyses. The effect sizes found in these studies tend to be very large.…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Some studies have explored the effectiveness of the theory with regard to identifying any user innovations. Thus, Franke and Shah (2003), Lüthje (2004), Lüthje et al (2002) and Morrison et al (2000) divided their samples into innovators and non-innovators as a dependent variable, and showed that lead user characteristics are systematically different in these two groups via t-tests and logit analyses. The effect sizes found in these studies tend to be very large.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Lüthje (2003) found that 48% of surgical innovations developed by surgeons in university clinics in Germany had been or would be produced as commercial products. Evaluators of the commercial potential of innovations developed by a sample of mountain bikers judged that 31% of the innovations would be "adopted by many users if produced" (Lüthje et al 2002).…”
Section: Review Of Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Sometimes, this user innovation can be source of a successful commercial product. Sports equipment such as the rodeo kayak [1], mountain bike [2], snowboard [3], and surfboard [4], medical equipment [5], juvenile products such as the baby jogger [6], services such as computerized commercial banking services [7], computer games [8], and films in the animation genre [9] are few examples where user innovations was a success.…”
Section: Introductionmentioning
confidence: 99%